Laparoscopic surgery for complex and recurrent Crohn's disease - Sevim, Yusuf; Akyol, Cihangir; Aytac, Erman; Baca, Bilgi; Bulut, Orhan; Remzi, Feza H. (BAISHIDENG PUBLISHING GROUP INC, 2017)
Crohn's disease (CD) is a chronic inflammatory disease of digestive tract. Approximately 70\% of patients with CD require surgical intervention within 10 years of their initial diagnosis, despite advanced medical treatment alternatives including biologics, immune suppressive drugs and steroids. Refractory to medical treatment in CD patients is the common indication for surgery. Unfortunately, surgery cannot cure the disease. Minimally invasive treatment modalities can be suitable for CD patients due to the benign nature of the disease especially at the time of index surgery. However, laparoscopic management in fistulizing or recurrent disease is controversial. Intractable fibrotic strictures with obstruction, fistulas with abscess formation and hemorrhage are the surgical indications of recurrent CD, which are also complicating laparoscopic treatments. Nevertheless, laparoscopy can be performed in selected CD patients with safety, and may provide better outcomes compared to open surgery. The common complication after laparoscopic intervention is postoperative ileus seems and this may strongly relate excessive manipulation of the bowel during dissection. But additionally, unsuccessful laparoscopic attempts requiring conversion to open surgery have been a major concern due to presumed risk of worse outcomes. However, recent data show that conversions do not to worsen the outcomes of colorectal surgery in experienced hands. In conclusion, laparoscopic treatment modalities in recurrent CD patients have promising outcomes when it is used selectively.
Keywords: Crohn's disease; Laparoscopic surgery; Complex disease management; Recurrent Crohn's disease